The MAC model about boredom according to westgate - Solf Zárate, Arturo (2021)
The basic characteristics of the MAC (Meaning and Attentional Components) model about boredom according to Westgate (2018) are presented. Its usefulness for the work of the psychologist. The possibility to apply it to any context. What is its theoretical foundation and basic research. Its links with some approaches and interventions in other areas of psychology. What future research can be facilitated with the model as a reference. Finally, it is used to analyze a collective reaction of citizens as a public expression of protest